Estimating systemic risk in the international financial system - Bartram, Söhnke M.; Brown, Gregory W.; Hund, John E. (Journal of Financial Economics, 2007)
This paper develops three distinct methods to quantify the risk of a systemic failure in the global banking system. We examine a sample of 334 banks (representing 80% of global bank equity) in 28 countries around five global financial crises. Our results suggest statistically significant, but economically small, increases in systemic risk. Although policy responses are endogenous, the low estimated probabilities suggest that the distress of central bankers, regulators and politicians about the events we study could be overstated and that current policy responses to financial crises could be adequate to handle major macroeconomic events.